Serum Uromodulin in Children and Adolescents with Type 1 Diabetes Mellitus and Controls: Its Potential Role in Kidney Health - Schiel, Ralf; Block, Mathias; Steveling, Antje; Stein, Günter; Lücking, Sarah; Scherberich, Jürgen (Experimental and Clinical Endocrinology & Diabetes, 2022)
Introduction Uromodulin is a kidney-specific tubular protein, and its assessment in serum (sUMOD) reveals the potential as a novel marker for function and the integrity of renal parenchymal cells and does not directly depend on the glomerular filtration rate. Early diabetic nephropathy parallels glomerular hyperfiltration, often leading to diagnostic misinterpretation. Moreover, traditional kidney function markers are not able to diagnose structural lesions. Recent data show that sUMOD is linked to glucose intolerance in adults. Thus, we launched to assess the hypothesis that sUMOD is also associated with kidney function, biometric data, and quality of metabolic control in children/adolescents with type 1 diabetes.Patients and methods Patients with type 1 diabetes (n=135) and healthy controls (n=69) were recruited to participate in the trial. Clinical, biometrical data, sUMOD, and other laboratory parameters were assessed.Results The mean concentrations of sUMOD in diabetic patients and controls were comparable (201.19±103.22 vs. 198.32±84.27 ng/mL, p=0.832). However, in contrast to healthy controls, sUMOD levels in patients with diabetes were associated with serum-creatinine (r=−0.368, p<0.0001), age (r=−0.350, p<0.0001), height (r=−0.379, p<0.0001), body weight (r=−0.394, p<0.0001), Body mass index (r=−0.292, p=0.001), daily insulin dosage (r=−0.300, p<0.0001), HbA1c (%) (r=−0.190, p=0.027), standardized HbA1c/IFCC (mmol/mol) (r=−0.189, p=0.028), and systolic (r=−0.299, p<0.0001) and diastolic (r=−0.235, p=0.006) arterial blood pressure.Conclusions Our study shows that children/adolescents with type 1 diabetes disclose similar sUMOD concentrations as healthy controls. Serum UMOD appears to indicate higher risks for kidney tissue remodeling and possibly subsequent cardiovascular alterations. However, further studies are mandatory to settle these findings.
Keywords: Serum uromodulin; ELISA; kidney biomarker; juvenile type 1 diabetes; risk assessment